MANAJEMEN KEUANGAN PENDIDIKAN PADA MASA PANDEMI COVID-19 PADA MA PLUS PAWITRA - yulianti, euis; zulwendra, reza; lutpi, sayal (Journal of Management Review, 2025)
The Covid-19 pandemic has changed many sectors, including education. One of the impacts is the management of education in the education financing sector during the Covid-19 pandemic. The balance between madrasa needs and income during the COVID-19 pandemic must be carefully planned. The purpose of this study was to determine the process of planning, implementing, and supervising the management of BOS funds at MA Plus Pawitra. The method in this study used descriptive qualitative research, with the research subjects being the Head of Madrasah, Treasurer of BOS, and the Madrasah Committee. The data collection technique used is the technique of observation, interviews, and documentation. The results of the study can be concluded that the planning process begins with filling out the Madrasah Self Evaluation (EDM). The results of filling out the EDM are used as material to determine the types of priority programs in the preparation of madrasah improvement and development plans as outlined in the electronic Madrasah Work Plan and Budget (e-RKAM). The implementation of the use of BOS funds is distributed every semester, the withdrawal of funds is carried out by the BOS Treasurer and the Head of Madrasah at Bank BNI, for use it is adjusted to the RKAM that has been made previously. Reports on the use of BOS funds are carried out every semester and given to the Commitment Making Officer (PPK). Supervision is carried out by the Madrasah Committee as an internal supervisor and the PPK of the Ministry of Religion of Tasikmalaya Regency as an external supervisor.